2019
DOI: 10.3390/s20010046
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and NH3 Gas-Sensing Properties of Double-Shelled Hollow ZnTiO3 Microrods

Abstract: A novel double-shelled hollow (DSH) structure of ZnTiO3 microrods was prepared by self-templating route with the assistance of poly(diallyldimethylammonium chloride) (PDDA) in an ethylene glycol (EG) solution, which was followed by calcining. Moreover, the NH3 gas-sensing properties of the DSH ZnTiO3 microrods were studied at room temperature. The morphology and composition of DSH ZnTiO3 microrods films were analyzed using scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…[28][29][30] ZnTiO 3 has received much attention because of its promising applications in NH 3 detection, photocatalysis, and lithium storage materials. [31][32][33] However, the short wavelength absorption and high charge recombination rate of pure ZnTiO 3 photocatalysts are still problems of low photocatalytic performance. To address these drawbacks, attempts have been made to modify ZnTiO 3 with atomic doping, [34] but the modified ZnTiO 3 still cannot effectively utilize sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] ZnTiO 3 has received much attention because of its promising applications in NH 3 detection, photocatalysis, and lithium storage materials. [31][32][33] However, the short wavelength absorption and high charge recombination rate of pure ZnTiO 3 photocatalysts are still problems of low photocatalytic performance. To address these drawbacks, attempts have been made to modify ZnTiO 3 with atomic doping, [34] but the modified ZnTiO 3 still cannot effectively utilize sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the titanium‐based perovskite oxides, ZnTiO 3 has attracted widespread attention in different frontier research fields due to its extraordinary potentials in electrode materials, [8] magnetic materials, [9] antibacterial materials, [10] gas sensors, [11] photocatalysis, [12,13] and heterogeneous catalysis [14,15] . It has been reported that cubic and hexagonal phases of ZnTiO 3 as catalyst support exhibit different catalytic performances in the steam reforming of methanol due to their different properties [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Tuning support composition, support morphology, doping of supports with elements of different valency, surface modification has been employed as efficient strategies to enhance the metal-support interaction to improve the catalytic activity. [7] As one of the titanium-based perovskite oxides, ZnTiO 3 has attracted widespread attention in different frontier research fields due to its extraordinary potentials in electrode materials, [8] magnetic materials, [9] antibacterial materials, [10] gas sensors, [11] photocatalysis, [12,13] and heterogeneous catalysis. [14,15] It has been reported that cubic and hexagonal phases of ZnTiO 3 as catalyst support exhibit different catalytic performances in the steam reforming of methanol due to their different properties.…”
Section: Introductionmentioning
confidence: 99%